Development of a PID controller for DC motor using Microsoft Visual Basic - Mohd Aizuddin, Abu Bakar (2008)
This main of this project is to develop a PID (Proportional, Integral, Derivatives) controller and interface with a device. The controller is PID and the software is Microsoft Visual Basic 6.0. The MATLAB software is used for simulation of this system. The methodology is divided into two parts which is software and hardware. The first part is simulation for this system by using Matlab software to determine the value of Kp, Ki and Kd. The range value for PID is determined by using Ziegler Nichols method. For second part is to interface the controller with hardware. The controller is using Microsoft visual basic 6.0 software. Then, the controller need to interface with DAQ card first. After interfacing success, the system can be implementing to servo motor. The feedback value can be received from servo motor encoder. After finished the first and second part, this system can be tuned up by using the PID value from simulation.